Cognitive interventions in Alzheimer's and Parkinson's diseases: emerging mechanisms and role of imaging. Issue 4 (August 2016) - Vemuri, Prashanthi; Fields, Julie; Peter, Jessica; Klöppel, Stefan
Abstract : Purpose of review: There has been recent debate about the lack of compelling scientific evidence on the efficacy of cognitive interventions. The goal of this study is to review the current state of cognitive interventions in Alzheimer's disease and Parkinson's disease, present emerging mechanisms, and discuss the role of imaging in designing effective intervention strategies. Recent findings: Cognitive interventions appear to be promising in Alzheimer's disease and Parkinson's disease. Although feasibility has been shown in mild cognitive impairment, early Alzheimer's disease, and mild to moderate Parkinson's disease, studies to investigate long-term efficacy and mechanisms underlying these interventions are still needed. Summary: There is a need to conduct scientifically rigorous studies to validate the efficacy of cognitive intervention trials. Future studies will greatly benefit from including longitudinal imaging in their study design. Imaging can be used to demonstrate the efficacy and mechanisms by measuring brain changes over the intervention period. Imaging can also be used to determine biological and disease-related factors that may influence the treatment response, that is, the effect modifiers. Consideration of effect modifiers will allow us to measure the treatment response in biomarkers and cognition with greater sensitivity and also aid in designing trials that will lead to better patient outcomes.